Psychosomatic consequences of violence in war conditions: analysis of the relationship with the type of trauma and the level of stress - Chaban, Олег; Олексієнко, Анна (Psychosomatic Medicine and General Practice, 2025)
Introduction. The ongoing war and socio-economic instability in Ukraine have led to an increase in the incidence and severity of violence, accompanied by chronic stress. Survivors of violence often develop psychological disorders (depression, anxiety, post-traumatic stress) and various psychosomatic symptoms, yet there is a lack of interdisciplinary research on this issue in the Ukrainian context. Aim. To examine the psychosomatic manifestations in adults who have experienced violence during wartime and analyze their relationship with the types of violence, level of life stress, and gender factors. Materials and Methods. A cross-sectional survey of 200 respondents was conducted via an anonymous online questionnaire. An author-designed checklist identified exposure to five types of violence (physical, sexual, psychological, economic, and violence by caregivers/educators). Psychological and somatic symptoms were assessed with the SCL-90-R questionnaire, and the level of life stress was measured using the Holmes-Rahe Social Readjustment Rating Scale. Participants were divided into an experimental group (n=178, with ≥2 signs of violence) and a control group (n=22, ≤1 sign). Nonparametric group comparisons (Mann-Whitney U test) and Spearman’s correlation analysis were performed with a significance level of p<0.05. Results. Psychological (emotional) violence was the most prevalent (88,5%). The average cumulative life stress score was 197 points, indicating a moderate stress level. The most frequent stressful events included changes in financial status, residence, and living conditions (each reported by 41.7%). According to the SCL-90-R, victims of violence showed a high level of psychological distress and psychosomatic complaints: their mean scores on primary symptom dimensions were substantially above normative values. The most common symptoms were headaches (66.7%), chronic fatigue and impaired concentration (62.5%), as well as muscle tension and chest pain. The violence-exposed group differed significantly from controls: for example, the average Holmes-Rahe stress score in victims was almost three times higher (212 vs 78; p<0.05), and their scores on 8 of 9 SCL-90-R scales were significantly elevated compared to individuals without traumatic experience (p<0.05). Correlation analysis confirmed that different types of violence have specific impacts on psychological symptoms. Notably, economic violence had the strongest association with somatization (ρ=0.37; p<0.05). Sexual violence correlated with a broad range of psychopathological symptoms (significant links with 10 of 12 SCL-90-R indices, especially hostility and anxiety (ρ≈0.26-0.32; p<0.05)). Physical violence also correlated with a broad range of psychopathological symptoms (significant links with 8 of 12 SCL-90-R indices, especially paranoid ideation, anxiety, and the total number of symptoms (ρ≈0.25-0.32; p<0.01). Psychological violence showed a positive correlation with hostility (ρ=0.31) and a weak inverse correlation with phobic anxiety (ρ=-0.15). Violence in the upbringing/education context had only weak associations, mainly with somatization and depression. Women in our sample were considerably more likely than men to have experienced sexual (25% vs 9%) and economic violence (50% vs 32%), whereas men more often reported physical (29% vs 16%) and caregiver-related violence (68% vs 53%). Although women generally constituted a larger proportion of victims, male victims exhibited more pronounced obsessive-compulsive (p=0.026), paranoid (p=0.014), and psychotic symptoms (p=0.028), as well as higher overall distress (GSI; p=0.046) than female victims. Conclusions. This study demonstrates a systemic relationship between the experience of violence and individuals’ psychosomatic health. In the context of war, exposure to violence coupled with chronic environmental stress greatly increases the risk of psychological and somatic exhaustion in survivors. The most pronounced mental health consequences are observed in cases of sexual, physical, and psychological violence. Female and male victims exhibit different response profiles, which necessitates a gender-sensitive approach in psychological care. These findings can be applied to improve violence screening in clinical settings and to develop targeted rehabilitation strategies for affected individuals.